El género Selaginella Pal.-Beauv. (Selaginellaceae, Lycopodiophyta) en el oeste del Estado de México, México - Abundiz-Bonilla, Leonor Ana María; Tejero-Diez, J. Daniel (Instituto de Ecología, A.C., 1990)
Field and laboratory studies indícate that there exist 14 species of the genus Selaginella in the western part of the State of México, México. A key to the species is included along with descriptions and data on distribution and ecological affinities.